Sams Teach Yourself Network Troubleshooting in 24 Hours, Second Edition - Feldman, Jonathan (Sams, 2002)
A practical, hands-on quide to network troubleshooting that emphasizes diagnostic techniques that both professionals and part-time network adminstrators can understand and use in their day-to-day activities. In today's pervasive network environment, many of these people are often responsible for fixing a network if it goes down. This book emphasizes fixing practical networking applications like shared printers, using the Internet, and sharing files. It does not get into the specifics of protocols or specific applications, but provides short, concise overviews of topics like wireless networking, Unix, Windows 2000, Novell Netware, routers, and firewalls.